High-quality economic development, green credit and carbon emissions - Li, Wei; Lin, Xiaoken; Wang, Hui; Wang, Shaowen (Frontiers in Environmental Science, 2022)
Carbon peaking and neutrality goals have been an important issue in China's economic development in recent years. here is increasing academic interest in ways to realize emission peak and carbon neutrality goals within a finite timeframe. As an important means of sustainable development, high-quality economic development and green credit are of great significance to achieve carbon peak and carbon neutrality. Based on the panel data of 29 provinces and cities in China from 2007 to 2020, spatial Durbin and semi-etric spatial lag models are adopted to investigate the impact of high-quality economic development on green credit and carbon emissions. This study also analyzes whether green credit plays a moderating role in the impact of high-quality economic development on carbon emissions through the moderating effect model. The results reveal that such development has a significant negative correlation with carbon emissions, and presents an “inverted U” -shaped nonlinear relationship. There is a significant negative correlation between green credit and carbon emissions, and an “n-type” nonlinear relationship. Finally, the moderating role of green credit in the impact of high-quality economic development on carbon emissions is analyzed. This study presents the following suggestions :(1)Give full play to the positive spillover effect of high-quality economic development between various regions, and build a complete high-quality economic development system, (2) Improve the green credit system, increase green credit funds, and promote green development.